Implementation and effectiveness of Swachhata Pakhwada activities by a tertiary care hospital in improving the health and hygiene promotion - Bhadoria, Pooja; T., Ramya; Kumar, Ram (International Journal Of Community Medicine And Public Health, 2025)
Swachhata Pakhwada, introduced under the Swachh Bharat Mission (SBM), plays a pivotal role in institutionalizing cleanliness and hygiene across various sectors, including healthcare. This paper reviews the implementation and effectiveness of Swachhata Pakhwada activities at AIIMS Rishikesh, assessing their impact on health promotion, waste management, and public awareness. The study highlights key initiatives such as cleanliness drives, community outreach, green initiatives, biomedical waste management, and hygiene awareness campaigns. Special focus is given to the role of Swachhata Special Campaigns in addressing emerging challenges beyond routine activities. By analysing achievements, challenges, and best practices, this paper provides insights into the long-term sustainability of hygiene initiatives in tertiary care institutions. The findings emphasize the importance of continuous engagement, resource allocation, and policy reinforcement to sustain and enhance the progress made under Swachhata Pakhwada.